A Pilot Randomized Controlled Trial of Text Messaging to Increase Tobacco Treatment Reach in the Emergency Department. Issue 9 (4th March 2021) - Abroms, Lorien C; Wu, Keng-Chieh; Krishnan, Nandita; Long, Michael; Belay, Sarah; Sherman, Scott; McCarthy, Melissa
Abstract: Introduction: Automated text messaging programs have been studied as a treatment tool, but have not been studied as an outreach tool to increase the reach of smoking cessation treatment. Aims and Methods: Two distinct text messaging programs were developed. One was aimed at connecting smokers to quitline phone counseling via text message (Text4Coach [T4C]) and the other was aimed at connecting smokers to a smoking cessation text messaging program (Text&Quit [T&Q]). Adult daily smokers with Medicaid insurance ( N = 80) were recruited from the Emergency Department at an urban hospital and randomized to T4C or T&Q. The primary outcome was program reach. Results: Outreach text messages were found to have moderately high uptake, with the majority of participants (63.8%) opting into their assigned tobacco treatment program and younger and female participants more likely to opt in ( p < .01). Receipt of the treatment portion of the program differed among the programs with 67.5% of T&Q receiving the treatment program and 27.5% of T4C receiving the program ( p < .001). Most participants across both groups replied to at least one message (71.3%) and very few unsubscribed from the service over the 3-week trial. The majority of participants reported overall satisfaction with their program (63.8%), found it helpful for quitting smoking (60.0%) and would recommend the program to a friend (62.5%). Overall, 11 (13.8%) participants reported being abstinent from smoking for the past 7 days at follow-up, with no differences between groups. Conclusions: Outreach text messages were found to have moderately high reach among Medicaid smokers. Larger trials are needed to evaluate the impact of such programs on helping low-income smokers quit. Implications: Automated text messaging programs have been tested as a treatment tool, but have not been tested as an outreach tool to increase the reach of smoking cessation treatment. This study tests a new way of conducting outreach to smokers in a health system through text messages. It tests the effect of outreach on (1) rates of opting in and (2) successful treatment delivery. Results may inform new models of providing outreach for tobacco treatment in health systems.